Mouse Acidic Chitinase Effectively Degrades Random-Type Chitosan to Chitooligosaccharides of Variable Lengths under Stomach and Lung Tissue pH Conditions - Wakita, Satoshi; Sugahara, Yasusato; Nakamura, Masayuki; Kobayashi, Syunsuke; Matsuda, Kazuhisa; Takasaki, Chinatsu; Kimura, Masahiro; Kida, Yuta; Uehara, Maiko; Tabata, Eri; Hiraoka, Koji; Seki, Shiro; et al. (Molecules (Basel, Switzerland), 2021)
Chitooligosaccharides exhibit several biomedical activities, such as inflammation and tumorigenesis reduction in mammals. The mechanism of the chitooligosaccharides' formation in vivo has been, however, poorly understood. Here we report that mouse acidic chitinase (Chia), which is widely expressed in mouse tissues, can produce chitooligosaccharides from deacetylated chitin (chitosan) at pH levels corresponding to stomach and lung tissues. Chia degraded chitin to produce N-acetyl-d-glucosamine (GlcNAc) dimers. The block-type chitosan (heterogenous deacetylation) is soluble at pH 2.0 (optimal condition for mouse Chia) and was degraded into chitooligosaccharides with various sizes ranging from di- to nonamers. The random-type chitosan (homogenous deacetylation) is soluble in water that enables us to examine its degradation at pH 2.0, 5.0, and 7.0. Incubation of these substrates with Chia resulted in the more efficient production of chitooligosaccharides with more variable sizes was from random-type chitosan than from the block-type form of the molecule. The data presented here indicate that Chia digests chitosan acquired by homogenous deacetylation of chitin in vitro and in vivo. The degradation products may then influence different physiological or pathological processes. Our results also suggest that bioactive chitooligosaccharides can be obtained conveniently using homogenously deacetylated chitosan and Chia for various biomedical applications.
Keywords: substrátová specifita; plíce; Mice; zvířata; chitinasy; Chitosan; random-type chitosan; koncentrace vodíkových iontů; difrakce rentgenového záření; Lung; Organ Specificity; X-Ray Diffraction; hydrolýza; chitosan; žaludek; Stomach; Chitinases; chitin; block-type chitosan; myši; oligosacharidy; Substrate Specificity; orgánová specificita; Animals; FACE method; chitooligosaccharides; acidic chitinase; Oligosaccharides; Hydrolysis; Hydrogen-Ion Concentration